A new association – multiple endocrine neoplasia type 1 and malignant peripheral nerve sheath tumor. Issue 1 (6th October 2014) - Preda, Veronica; Sywak, Mark; Learoyd, Diana
<x xml:space="preserve">Abstract</x> We report a patient with multiple endocrine neoplasia type 1 (MEN‐1) and an aggressive malignant peripheral nerve sheath tumor (MPNST) arising from a ganglioneuroma of the adrenal gland. Patients with MEN‐1 require careful consideration of other tumor associations, including MPNST, as it can portend a poor prognosis. MEN‐1 and MPNST have not been reported.